Mechanism of Longevity Extension of Caenorhabditis elegans Induced by Schizophyllum commune Fermented Supernatant With Added Radix Puerariae - Deng, Yongfei; Liu, Han; Huang, Qian; Tu, Lingyun; Hu, Lu; Zheng, Bisheng; Sun, Huaiqing; Lu, Dengjun; Guo, Chaowan; Zhou, Lin (Frontiers in Nutrition, 2022)
As the principal metabolic component of the edible medicinal fungus Schizophyllum commune (S. commune), schizophyllan (SPG) shows excellent immune, anti-cancer and moisturizing properties. However, the low yield and complex purification process of SPG limit the application of S. commune in food, pharmaceutical and cosmetic industries. We selected the edible medicinal plant Radix Puerariae (RP) as the fermentation substrate to further expand the application of S. commune and endow the fermented products with potent biological activities by biotransformation. In this study, the effect of fermented supernatant cultured from S. commune in RP-supplement medium (SC-RP) on extending the lifespan and improving stress resistance of Caenorhabditis elegans (C. elegans) were examined. Additionally, the underlying molecular mechanisms of SC-RP were explored. The lifespan of C. elegans increased by 24.89% when C. elegans was treated with SC-RP at 10 μg/mL (p < 0.01). SC-RP prolonged the healthspan of the nematode, including reducing lipofuscin levels, improving mobility and enhancing resistance to oxidative stress and heat shock. Moreover, superoxide dismutase and catalase activities increased for SC-RP-treated C. elegans, whereas the intracellular levels of thiobarbituric acid reactive substances (TBARS) and reactive oxygen species (ROS) were attenuated. The anti-aging mechanism of SC-RP on the nematode involved genes daf-2, daf-16, sod-3, skn-1, gst-4 and clk-1 but not age-1 and mev-1. The results suggest that SC-RP extends the healthspan of C. elegans via the IIS pathway, SKN-1/Nrf2 pathway and mitochondrial metabolism pathway. SC-RP is a potential candidate to improve aging and aging-related symptoms.